Field lab SME competitiveness - internationalization strategy - Fortunato, Carolina Amaral Cabrita Ramalhão (2020)
or the completion of the Work Project, an In-Depth Analysis was conducted. The ultimate purpose was to thoroughly analyze Norway, as a potential country to internationalize to. For that analysis, four dimensions were considered and studied – the quality of contacts in the country, the market sales potential, the competitive environment and the market entry conditions. So as to make a sustained decision, a framework was developed in order to compare the five countries and understand which one would be the most promising for EGG Electronics.